(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The most prevalent cause of death linked to cancer in the lungs is still lung cancer. Lung cancer specifically the non-small cell lung cancer (NSCLC) is a form of lung cancer which is widely common around 85% of all lung cancer patients are diagnosed with NSCLC. NSCLC also is further classified into multi histological subtypes which are adenocarcinomas, squamous cells carcinoma, large cell carcinoma, and mixed. The treatment of NSCLC relies heavily on systemic chemotherapy using platinum based drug.AN When treating NSCLC, a number of techniques and challenges are involved. These methodologies include targeted therapy, immunotherapy, or the combination of both, with the goal of targeting and inhibiting certain molecular pathways, or expanding the extent of the patient’s defence response. In treating NSCLC, this is one of the biggest issues. Targeted therapies were designed to improve NSCLC therapeutics, however, it has proven difficult due to early emergence of resistance. Resistance mechanisms including targeted drug resistance development and trait variations including gene mutations and anomalies specific for each NSCLC subtype Relative differences in the amount of NSCLC there is also explains the reasons why treatment targeting each NSCLC subtype is difficult. In addition to this, the age and sex of the patient will play a significant role in making treatment decisions as well as the outcomes of the NSCLC treatment in this study. To conclude, a synopsis of the various approaches being used in tackling NSCLC and the corresponding difficulties including that of each type of therapy has been presented.